(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article analyzes the problems of national security in the Kyrgyz Republic. Today, in the process of a changing world, the problem of Kyrgyzstan’s national security has acquired an urgent and global character. All this is due to the fact that during the transformation of society, value orientations, attitudes towards the integrity of the state, internal and external threats and patriotism of citizens of the Kyrgyz Republic have changed. The problems of national security of the Kyrgyz Republic such as terrorism, religious radicalization of social groups, individuals are relevant not only in relation to political management, but also to the modern historical period of the Kyrgyz Republic.